PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN PASAR KUMANDANG - Rysca Indreswari; Dyah Yuni Kurniawati; Irsyadul Ibad (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2019)
Bongkotan Hamlet is the smallest hamlet located in Bojasari Village, Kertek District, Wonosobo Regency. In this place there is a site of Bongkotan Temple which is the legacy of the Syailendra Dynasty. Unfortunately, this rich history has not been managed optimally. Seeing this condition, Sigit Budi Martono along with creative activists in Bongkotan Hamlet invited the community to participate in reviving the tourism potential. The idea was initiated by creating the Kumandang Market located on Bongkotan hill, just across the Bongkotan Temple site area. It is intended that the existence of temple sites and village markets can be mutually integrated so that it can attract tourists to visit. Finally, after going through a preparatory process involving the local community, the official Kumandang Market was held on June 24, 2018 by utilizing the momentum of the Eid Mubarak holiday. Until now, the Kumandang Market has been held 18 times with the number of visitors increasing every week. This shows the existence of community participation in the development of the Kumandang Market. Based on the results of the study, community participation in the development of the Kumandang Market is indicated by the participation in decision making in Kumandang Market planning, participation in the implementation of the Kumandang Market, participation in taking utility of Kumandang Market, and participation in evaluating the Kumandang Market.